Suppose the government imposes a tax on each unit of output produced of $t. What is the firm’s new profit maximizing level of output?

The question suggests the use of comparative to determine how a change in tax affects a change in output. The firm would operate under perfect competition conditions.

I started to answer it this way.

Before Tax:
π = revenue - costs
π = pq - C(q)
dπ/dq = p - C'(q)

Set dπ/dq for profit-maximisation
0 = p - C'(q)
p = C'(q)
p = MC

After Tax:
π = revenue - costs - tax
π = pq - C(q) -tq
dπ/dq = p - t - C'(q)

Set dπ/dq for profit-maximisation
0 = p - t - C'(q)
p = t + C'(q)
p = t + MC

Next I would try to find out how quantity changes with tax t by taking derivates? Any ideas?


2 Answers 2


you can do this using comparative statics and envelope theorem. The profit function specification was correct given the assumptions, let me just rewrite it as:

$$\pi (q,t) = p q - C(q) - tq$$

However, given the above we also know that the optimal quantity will depend also on a tax rate, so we will have $q^* = q(t)$.

Now by envelope theorem:

$$\frac{\pi^*(t)}{dt} = \pi'_2(q^*(t),t) = - Q^*(t) $$

So the optimal level of output given the tax $t$ will depend inversely on change in profit when the tax rate changes or $-\pi'_2(q^*(t),t) = Q^*(t)$.


Intuitive/graphical answer:

A tax per unit of production basically increases marginal cost of production at each level of production. Effectively, it shifts MC curve up by $t$ units. Now we know that in a competitive market, firms are price takers (so horizontal demand curve). So they'll produce till the point MC touches $P$. Given that MC is increasing$^\dagger$, an upward shift in in MC curve means decrease in output. More the shift more the decrease in output.

enter image description here

$^\dagger:$ In a perfect competition, decreasing MC is not possible because there is infinite demand for each firm - so firm will always operate in increasing MC part

Mathematically: You have already found the FOC, which states that at tax rate $t$, output supplied $q^*(t)$ will satisfy the following condition:

\begin{align} C'(q^*(t))+t-P&=0 \\ \end{align}

Differentiating this equation w.r.t $t$: \begin{align} \frac{dC'(q^*(t))}{dt}+1&=0 \\ \frac{\partial C'(q^*)}{\partial q^*} \cdot \frac{dq^*}{dt}&=-1 \\ \frac{dq^*}{dt}&=-1/C''(q^*)<0 \end{align}

The last step uses the SOC:



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.